3-Year Follow-Up of Arthroscopic Debridement and Interposition with Acellular Allograft Dermal Matrix for Ankle Arthritis with Anterior Impingement. Issue 4 (November 2022) - Miller, Roslyn
Category: Ankle Arthritis; Ankle; Arthroscopy Introduction/Purpose: Early ankle arthritis can present with pain and anterior impingement. Younger, active patients who have exhausted conservative treatment have two options; ankle arthrodesis or ankle arthroplasty. Both are major procedures that have pros and cons. Revision surgery for both of these procedures is a major undertaking. Therefore, fit active patients who are under 65, may benefit from a less invasive procedure of anterior ankle arthroscopy and debridement. There is a risk, however that debridement alone, may inadvertently lead to the acceleration of joint degeneration. Thus the arthroscopic insertion of an acellular allograft dermal matrix acts as a 'cushion' to the joint surface and 'buy some time' for the patient to delay major surgery while having a reduction in their symptoms of pain and stiffness. Methods: Patients had surgery performed as a day case under general anaesthetic and tourniquet. No joint distraction was used. Two anterior portals were utilised; anetermedial and anterolateral. A 4mm arthroscope was used to visualise the joint surface. A arthroscopic shave and burr were used to remove any scar soft tissue and tibial and talar osteophytes. Any lateral ankle instability of the ATFL ligament, confirmed, clinically and with MRI imaging, was addressed with stabilisation using arthroscopic placement of an augmented stabilization with synthetic brace. A piece of acellular allograft dermal matrix was cut to size and place through one of the anterior portals onto the joint surface of the talus. The allograft was held in place with tisseal glue. Post-operatively the patient was place in a moonboot which was worn day and night for two weeks, then day only for a further two weeks, non weight- bearing. Three months of physiotherapy followed. Results: The majority of patients had an improvement in their range of motion. Most had reduction in their symptoms of pain. Patients who were less active appeared to have a longer duration of benefit versus those who were keen to return to full activity as quickly as possible. There was no incidence of infection or septic arthritis. One allograft tranlated anteriorly out of the joint space, resulting in a degree of impingement. Patients who wanted to consider further surgery presented on average two to three years after the index procedure. Conclusion: Anterior ankle arthroscopy with arthroscopic debridement of osteophytes and acellular allograft dermal matrix interposition, is a more minor procedure than ankle arthrodesis or ankle arthroplasty. This provides patients with an alternative to major surgery at a time in their lives where they wish to delay major intervention. The most challenging aspect of the procedure is inserting the acellular allograft dermal matrix through a small anterior portal and inserting it into the joint surface.